High-Throughput Analytical Techniques for Multiresidue, Multiclass Determination of 653 Pesticides and Chemical Pollutants in Tea–Part IV: Evaluation of the Ruggedness of the Method, Error Analysis, and Key Control Points of the Method. (27th November 2019) - Fan, Chun-Lin; Li, Yan; Chang, Qiao-Ying; Pang, Guo-Fang; Kang, Jian; Cao, Jing; Zhao, Yan-Bing; Li, Nan; Li, Zeng-Yin
Abstract: A 3 month study was conducted on the ruggedness of a multiresidue method for accuracy and stability. The results indicate that in terms of Youden pair ratios of 201 pesticide aged tea samples falling approximately within 1.00–1.20 of the ratio of theoretical spraying concentrations, the differences donot exceed 5% for percentages made up by ratios of the fixed values obtained by two kinds of instrumentsfor two teas and those made up by 18 circular determinations. However, regarding two kinds of SPE cartridges, the Cleanert TPT cartridgeis higher than the ENVI-CARB + primary secondary amine (PSA) cartridge by 10%. Pertaining to RSD values of "parallelsamples" and whether it is green tea or Woolong tea, the percentages of RSD ≤15% values ofthe parallel samples all exceed 88%. Whether it isthefirst or circular determination for two teas andanalytical results from two kinds of instruments, the percentages of RSD ≤15% values have a difference of less than 6%, while the TPT cartridge is betterthan ENVI-CARB + PSA by above 6% for the two cartridges. Concerning RSDs of Youden pair ratios, RSD ≤15% values have a proportion exceeding 85% for both green tea and Woolong tea, and the percentageis greater than 87% whether it is for two kinds of SPE cartridges or two kinds of instruments. In terms of Youden pair ratios and the classified statisticalanalysis of the ruggedness data of parallel samples, theproportion of RSD ≤15% values of Youden pair ratios is 8% higher for the TPT cartridge than the ENVI-CARB + PSA cartridge; the proportion of RSD ≤15% values of parallel samples is 6.2% higher for the TPT cartridge than the ENVI-CARB + PSA cartridge. Data show no marked differences for two teas and two kinds of instruments. A comparison of the aforementioned aspects finds that good ruggedness was obtained with both SPE cleanup methods, and the results from the TPT cartridge are better than those from the ENVI-CARB + PSA cartridge.